HUBUNGAN PENGETAHUAN DAN ASUPAN ZAT BESI (FE) TERHADAP IBU HAMIL PENDERITA ANEMIA - Dery Windika Ramadhani (Yayasan Pendidikan Medika Indonesia, 2021)
Anemia is a condition in which the level of hemoglobin (Hb) in the blood is less than normal. Anemia in pregnant women is still a health problem in Indonesia. Based on the 2018 Riskesdas report, the prevalence of anemia in Indonesia is 48.9%. The most common cause of anemia in pregnant women is knowledge and lack of iron intake. The purpose of this study was to determine the relationship between knowledge and intake of iron (Fe) on pregnant women with anemia. The method used is a literature review by searching for the keywords anemia, knowledge, and iron intake on Google Scholar and Pubmed. Searching literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From several studies conducted, it was found that knowledge and intake of iron (Fe) had a significant relationship to the incidence of anemia in pregnant women.